2011
DOI: 10.1007/s10620-011-1989-z
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of MYO5B Promotes Invasion and Motility in Gastric Cancer Cells

Abstract: The expression of MYO5B was downregulated in gastric cancer and inactivation of MYO5B may contribute to tumorigenesis. Therefore, MYO5B may become an important biomarker for gastric cancer in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…However both proteins were selectively expressed in the NEC cell lines, suggesting specific function in epithelial-like cells. The vesicle transport function of MYO5B may be coordinated by complex formation with RAB25 and/or RAB11A (r = 0.49) [85] (Figure 14). …”
Section: Resultsmentioning
confidence: 99%
“…However both proteins were selectively expressed in the NEC cell lines, suggesting specific function in epithelial-like cells. The vesicle transport function of MYO5B may be coordinated by complex formation with RAB25 and/or RAB11A (r = 0.49) [85] (Figure 14). …”
Section: Resultsmentioning
confidence: 99%
“…Myo5b regulates membrane trafficking and cell polarity in association with Rab8 and Rab11, and downregulated expression of Rab11 and Myo5b has been linked to migration and invasion in gastric cancer. 48 Moreover, upregulation of its paralog Myo5a has been associated with malignant transformation in melanoma. 49 We also identified mutations in other steps of Rab-and Rac/Rho- .…”
Section: Discussionmentioning
confidence: 99%
“…MYO5A expression levels are increased in colorectal cancer in response to the transcription factor Snail [88], and it was suggested that its interaction with the pro-apoptotic protein Bmf, helps to prevent apoptosis as cells become less adhesive and invade the surrounding tissue. Decreased levels of MYO5B are associated with gastric cancer [89,90] and microvillus inclusion disease, a rare homozygous recessive disease [91]. Loss of MYO5B affects apical cargo protein transport in intestinal cells, which in turn causes intestinal brush border atrophy.…”
Section: Class 5 6 10 and 19 Myosin Isoformsmentioning
confidence: 99%